2021
DOI: 10.1186/s43042-021-00154-z
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of CCAAT/enhancer binding protein-alpha (CEBPA) expression in the bone marrow of acute myeloid leukemia patients

Abstract: Background Acute myeloid leukemia (AML) is a heterogeneous malignant disease characterized by accumulation of different types of mutations commonly the CCAAT/enhancer binding protein-alpha (CEBPA). However, the dysregulations of CEBPA expression in AML is still a debatable issue. The aim of the current study was to assess CEBPA gene expression in bone marrow (BM) aspiration specimens of 91 AML patients, compared to 20 control donors of bone marrow transplantation (BMT), using RT-PCR. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Moreover, it had been reported that miR-34a induced cell apoptosis and hindered autophagy by inhibiting the expression of high-mobility group protein 1 (HMG-1) or Histone deacetylase 1 (HDAC1) enzyme [ 40 ]. Additionally, MiR-34a was reported to be a downstream target of the C/EBPα gene which has a critical function in the development and progression of AML [ 41 , 42 ]. Therefore, upregulating miR-34a in AML patients with C/EBPα mutations could be an effective line of treatment [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it had been reported that miR-34a induced cell apoptosis and hindered autophagy by inhibiting the expression of high-mobility group protein 1 (HMG-1) or Histone deacetylase 1 (HDAC1) enzyme [ 40 ]. Additionally, MiR-34a was reported to be a downstream target of the C/EBPα gene which has a critical function in the development and progression of AML [ 41 , 42 ]. Therefore, upregulating miR-34a in AML patients with C/EBPα mutations could be an effective line of treatment [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides these changes, FLT3-ITD and DNMT3A mutations are the most common in NK AML [2]. Additionally, FLT3 expression is linked to that of CEBPA [3,4]. Due to these findings, NPM1, FLT3, CEBPA, and DNMT3A genes were chosen for this review.…”
Section: Introductionmentioning
confidence: 99%